1980
DOI: 10.1037/0021-843x.89.2.299
|View full text |Cite
|
Sign up to set email alerts
|

An MMPI comparison of polydrug and heroin abusers.

Abstract: Researchers recently have resurrected the relevance of the addiction-prone personality hypothesis for explaining drug abuse by faulting previous studies for failing to control non-drug-related subject background characteristics. This notion was tested by comparing Minnesota Multiphasic Personality Inventory clinical and content scores of polydrug and heroin abusers under conditions in which covariates were controlled and not controlled. The covariates age, education, socioeconomic status, and admission status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…To some, personality may" not seem useful in considering suitability of treatments or likely outcomes, while the term "addictive personality" is also particularly associated with one model of treatment, the Minnesota method "12-step" approach [2]. In that form of counselling it is used as much to convey to individuals the risk that they may transfer from one drug of dependence to another as to imply a definite scientifically-proven predisposition, and indeed research using psychological rating instruments for personality has generally failed to find a consistent collection of personality features in drug users [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…To some, personality may" not seem useful in considering suitability of treatments or likely outcomes, while the term "addictive personality" is also particularly associated with one model of treatment, the Minnesota method "12-step" approach [2]. In that form of counselling it is used as much to convey to individuals the risk that they may transfer from one drug of dependence to another as to imply a definite scientifically-proven predisposition, and indeed research using psychological rating instruments for personality has generally failed to find a consistent collection of personality features in drug users [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of the current study was to extend research on ethnic MMPI differences from heroin addicts and chronic alcoholics to polydrug abusers. Polydrug abusers have been noted to differ in personality from heroin addicts (e.g., Penk, Woodward, Robinowitz, & Parr, 1980). The general hypothesis tested was that black polydrug abusers would self-report less psychopathology on the MMPI than would white polydrug abusers.…”
mentioning
confidence: 99%
“…Similarly, Holland [71] found neurotic concerns and psychopathic tendencies to be critical in differentiating types of drug abusers. In a comparison of polydrug and heroin abusers, Penk et al [72] found heroin users to score higher on authority conflict, whereas polydrug users reported more organic symptoms and were generally more deviant on the MMPI clinical scales.…”
Section: Dimensions That Discriminate Between Populationsmentioning
confidence: 99%